If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6h + 8 = 5h Reorder the terms: 8 + 6h = 5h Solving 8 + 6h = 5h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-5h' to each side of the equation. 8 + 6h + -5h = 5h + -5h Combine like terms: 6h + -5h = 1h 8 + 1h = 5h + -5h Combine like terms: 5h + -5h = 0 8 + 1h = 0 Add '-8' to each side of the equation. 8 + -8 + 1h = 0 + -8 Combine like terms: 8 + -8 = 0 0 + 1h = 0 + -8 1h = 0 + -8 Combine like terms: 0 + -8 = -8 1h = -8 Divide each side by '1'. h = -8 Simplifying h = -8
| (11x+4)=180 | | x^2-6x+y^2-4y-13=0 | | 6m(m+16)(m-13)=0 | | .25(8x+28)-19=-.40(30x-45) | | 10-7s=-3s-2s-10 | | 42=2x+6 | | 13x-(9+2(x+4))= | | -69-5x=3x+27 | | 1/1.75-2 | | -2-3y+2y=-13 | | 23-2c=14 | | 37/22= | | -9w=-18-8w | | 1/3(3.14)5(5)(12) | | 9=-3/4x | | -10+3y=10+8y | | 6(r+6)=126 | | 60+5x=x | | x+237=895 | | 2x-(3x-6)=5 | | 2f(x)=7x-5 | | 8x=6x+2x | | 4x+7=.5(8x+12)+1 | | 3/20p=5 | | 0.4x-0.3x+0.4x=2 | | 144+16x=x | | 1/3j=9j | | -5(v+2)+2v+6=6v+10 | | 2v=6v-8 | | -9w=-8-8w | | b-4.7=3.5 | | ∞/∞ |